Pengaruh Dosis Ampas Kopi dan Pupuk KCl Terhadap Pertumbuhan dan Hasil Tanaman Bawang Merah - Ruhalena Wilis; Novi Mailidarni; Sarah Amalia (Jurnal Agrotek Lestari, 2025)
This study aimed to determine the optimal doses of coffee grounds and KCl fertilizer, as well as their interaction effects, on the growth and yield of shallot (Allium cepa L.). The experiment was arranged in a Randomized Complete Block Design (RCBD) with a 4 × 3 factorial arrangement and three replications. The first factor was the dose of coffee grounds (A0= 0 ton ha⁻¹, A1= 2 ton ha⁻¹, A2= 4 ton ha⁻¹, and A3= 6 ton ha⁻¹), and the second factor was the dose of KCl fertilizer (K1= 100 kg ha⁻¹, K2= 200 kg ha⁻¹, and K3= 300 kg ha⁻¹). The observed parameters included plant height and number of tillers per clump at 15, 30, and 45 days after planting (DAP), as well as fresh tuber weight, number of tubers, and dry tuber weight per clump. The results showed that the application of coffee grounds had a highly significant effect on plant height, number of tillers, fresh tuber weight, and dry tuber weight per clump, and a significant effect on the number of tubers per clump. The application of KCl fertilizer had a highly significant effect on plant height at 15 and 30 DAP and on the number of tillers at 30 DAP, but had no significant effect on plant height at 45 DAP, the number of tillers at 15 and 45 DAP, or tuber-related parameters. A significant interaction between coffee grounds and KCl fertilizer was observed for plant height at 15 DAP and for the number of tillers at 30 and 45 DAP. These findings suggest that the combination of coffee grounds and KCl fertilizer can improve vegetative growth and yield performance of shallots, highlighting the potential of organic–inorganic nutrient integration for sustainable crop production.Keywords: Coffee Grounds, Potassium Chloride (KCl), Shallot (Allium cepa L.), Plant Growth, Yield